Information Exposure and Career Understanding on ‎Marketing Interest: Mediation of Career Perception and Self-‎Efficacy Moderation - Happy Cantika Putri; M Fathur Rahman (JPI: Jurnal Pustaka Indonesia, 2026)
This study examined associations between information exposure, career prospect understanding, career prospect perception, self-efficacy, and students’ present interest in their chosen Marketing program at SMK Negeri 9 Semarang. Given the cross-sectional, self-report design, temporal ordering and causal inference cannot be established. A total of 107 tenth-grade Marketing students were recruited through total population sampling for the 2025/2026 academic year. Questionnaire data were analyzed using PLS-SEM in SmartPLS 4.1.1.8, with hypothesis testing via bootstrapping with 5,000 subsamples. Information exposure was positively associated with both career prospect perception and departmental interest. Career prospect understanding was strongly associated with career prospect perception but showed no significant direct association with interest. Career prospect perception and career decision-making self-efficacy each independently and positively predicted students’ interest. Career prospect perception partially mediated the information exposure interest association (indirect effect: β = 0.081, 95% CI [0.005, 0.157]) and fully mediated the career prospect understanding interest association (β = 0.177, 95% CI [0.066, 0.288]). The self-efficacy moderation was not supported (β = −0.060, 95% CI [−0.136, 0.016]). These findings suggest that students’ interpretations of career prospects, rather than factual understanding alone, are central to translating career information into academic interest, consistent with Social Cognitive Career Theory’s emphasis on self-efficacy and outcome expectations. However, the single-school sample, cross-sectional design, and self-reported measures limit causal interpretation and generalizability. Future longitudinal and multisite studies should test the temporal pathways, incorporate objective measures, and examine additional contextual moderators.